Social entrepreneurship in India : quarter idealism and a pound of pragmatism - Shukla, Madhukar (Sage, 2020)
"What makes a social entrepreneur? A handful of pragmatism with a generous dose of idealism. How does one recognize a social entrepreneur? Look for the ones solving social problems strategically. Who do they serve? Under-served markets and communities. How are they different from other change agents? They have entrepreneurial thinking, sensitivity to social issues and loads of compassion for fellow human beings. With lessons from 120 real-life examples of Indian social ventures and entrepreneurs, and practical insights into their successful models, this book dissects the phenomenon of 'social entrepreneurship' and highlights how ordinary entrepreneurs solve some of the most critical social problems strategically. 'Highly recommended for individuals, donors and policymakers seeking inspiration and ideas on how to build an ecosystem that promotes sustainable enterprises with purpose and soul.' M Hari Menon, India Country Director, Bill & Melinda Gates Foundation"--